Foresight of teachers' professional challenges - L. A. Novopashina; E. G. Grigorieva; D. V. Kuzina (Russian State Vocational Pedagogical University, 2022)
Introduction. The search for new tools, methods of research and forecasting of teachers' professional challenges is conditioned by the development of the Russian education system and the tasks to develop teachers' competencies. This article presents a research solution for predicting the professional challenges faced by teachers in the regional education system using foresight methods.Aim. The current research aims to predict the challenges of teachers' professional activity, considering the uncertainty of the formation of their foresight competencies.Methodology and research methods. The foresight methodology was chosen as a methodological basis for predicting teachers' professional challenges. The first experience of technological foresight presented by B. R. Martin, developed in different countries, spheres and industry systems (M. Hilbert, Y. Kishita, I. Miles, J. Othmer, C. Reimers-Hild, A. Magruk, etc.), has found its application in education (A. Havas, V. Munigala, J. Rong, Sánchez-Torres J. M., Sjodin, A. Yaver, etc.) and modern studies of professional competencies (M. Rieckmann, L. M. Andriukhina, E. F. Zeer, A. Kononyuk, L. E. Kurneshova, V. P. Smorchkova, etc.). This research is the first implementation of foresight methodology to study the education system of the Krasnoyarsk Territory. The prototype for the development of tools was the experience and materials of foresight research in Finland. In the course of the study, 241 individual interviews were conducted with the representatives of various stakeholders in the development of education - students of the pedagogical university, teachers and parents. The most active part and the largest share were teachers (77%), students - future teachers (15%) and parents (8%).Results. As a result of the study, it was found that the main challenge in the future will be the lack of competencies and skills of teachers to apply the necessary techniques and technologies. From the teachers' point of view, the main challenge in the future will be the lack of time for the necessary changes. From the point of view of future teachers, the main challenges of teachers will be the lack of desire and motivation on the part of students and teachers, lack of finance provision, equipment, resources. From the point of view of parents, the main difficulty in the future will remain excessive bureaucratisation of the learning process. In their opinion, the lack of desire and motivation on the part of students and teachers, as well as the lack of competency of teachers to apply the necessary techniques and technologies, are the main challenges of teachers.Scientific novelty. The research is aimed at solving the issues of choosing and adapting foresight methods in conditions of uncertainty of foresight competencies of its participants. The study promotes the possibility of expanding the range of stakeholders and considers the limitations of the spread of foresight technologies in Russia. The research demonstrated the possibility of predicting the assessment of teachers' professional challenges, which contributes to the foresight study of competencies.Practical significance. The received forecast about the professional challenges faced by teachers will provide the support to adjust the existing system of professional development of teaching staff and to lay the foundation for regional monitoring.